1997
DOI: 10.1128/aac.41.12.2680
|View full text |Cite
|
Sign up to set email alerts
|

Lobucavir is phosphorylated in human cytomegalovirus-infected and -uninfected cells and inhibits the viral DNA polymerase

Abstract: Lobucavir (LBV) is a deoxyguanine nucleoside analog with broad-spectrum antiviral activity. LBV was previously shown to inhibit herpes simplex virus (HSV) DNA polymerase after phosphorylation by the HSV thymidine kinase. Here we determined the mechanism of action of LBV against human cytomegalovirus (HCMV). LBV inhibited HCMV DNA synthesis to a degree comparable to that of ganciclovir (GCV), a drug known to target the viral DNA polymerase. The expression of late proteins and RNA, dependent on viral DNA synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…It has been reported that GCV is significantly phosphorylated by HCMV UL97, a viral protein kinase, in the virus-infected cells (19,20,23,35), like the phosphorylation by HSV-l TK in the HSV-l-infected cells. The finding that the ECso of C.OXT-G in HCMV-infected cells as well as in UL97-deficient HCMV-infected cells was equivalent to that observed in HSV-l TK --infected cells (21,36) indicated that C.OXT-G was not efficiently phosphorylated by the viral kinases, including UL97, whereas the basal phosphorylation might consistently occur. Neither was additional phosphorylation of C.OXT-A expected in HCMV-infected cells because of the similar level of its ECso to that of C.OXT-G (21); however, 3'F-C.OXT-A exhibited a l-log-more potent ECso than that of C.OXT-A (29).…”
Section: Antiviral Potency Of3'f-coxt-amentioning
confidence: 87%
See 2 more Smart Citations
“…It has been reported that GCV is significantly phosphorylated by HCMV UL97, a viral protein kinase, in the virus-infected cells (19,20,23,35), like the phosphorylation by HSV-l TK in the HSV-l-infected cells. The finding that the ECso of C.OXT-G in HCMV-infected cells as well as in UL97-deficient HCMV-infected cells was equivalent to that observed in HSV-l TK --infected cells (21,36) indicated that C.OXT-G was not efficiently phosphorylated by the viral kinases, including UL97, whereas the basal phosphorylation might consistently occur. Neither was additional phosphorylation of C.OXT-A expected in HCMV-infected cells because of the similar level of its ECso to that of C.OXT-G (21); however, 3'F-C.OXT-A exhibited a l-log-more potent ECso than that of C.OXT-A (29).…”
Section: Antiviral Potency Of3'f-coxt-amentioning
confidence: 87%
“…This suggested that C.OXTs might exert their antiviral activities mainly at steps preceding their incorporation into viral DNA strands. It has been reported previously that the triphosphate form of C.OXT-G, C.OXT-G-Tp, acts as a potent competitive inhibitor of HCMV polymerase, of which the Ki was estimated to 5 nM in contrast to the 0.22-14~M for human DNA polymerase-a; C.OXT-G-TP also acts as a potential chain terminator as a consequence of its incorporation into viral DNA strands (II, 15,36,37). The present study suggested that the inhibition of viral polymerase is very likely to be of greater importance than the chain termination function in accounting for the antiviral potency.…”
Section: Antiviral Potency Of3'f-coxt-amentioning
confidence: 99%
See 1 more Smart Citation
“…Novel antiviral compounds such as benzimidazole (508), adefovir (504), and lobucavir (461) are currently under investigation and might further improve the management of CMV infection. Moreover, antisense oligonucleotides complementary to RNA transcripts of IE genes provide a novel mechanism of inhibition for viral replication (11).…”
Section: New Anti-cmv Drugsmentioning
confidence: 99%
“…табл. 2), активен в отношении ВПГ-1, ВПГ-2, ВВЗ, ЦМВ, вируса гепатита В и ВИЧ [42][43][44]. Концентрации ЛБВ, эффективные в отношении ВПГ-1, ВПГ-2 и ЦМВ in vitro [42], ниже аналогичных величин для АЦВ.…”
Section: Introductionunclassified